2013
DOI: 10.1038/srep03473
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of VEGF-C and Tumor Markers in Bronchoalveolar Lavage Fluid for Lung Cancer Diagnosis

Abstract: A total of 87 patients were enrolled and bronchoalveolar lavage fluid (BALF) samples were obtained from all subjects. A significant difference was found in BALF VEGF-C level between patients with squamous cell carcinoma and benign diseases (P = 0.043). In addition, the concentration of NSE in BALF form the malignant group was significantly higher compared with that of the benign groups (P = 0.018). However, no statistical difference was observed in BALF CEA (P = 0.375) or CYFRA21-1 (P = 0.838) between lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The utility of cytokines in bronchoalveolar lavage fluid (BALF) for differential diagnosis of lung cancer has been described in several studies6789101112. In our previous reports, we also observed that the levels of vascular endothelial growth factor (VEGF) and neuron-specific enolase (NSE) were significantly higher in BALF of lung cancer patients than in that of patients with benign diseases1314. Recently, transforming growth factor (TGF)-β1, interleukin (IL)-6, and tumor nectosis factor (TNF)-α were suggested in published studies as possible diagnostic biomarkers of lung cancer due to their higher concentrations in serum of lung cancer patients151617.…”
mentioning
confidence: 92%
“…The utility of cytokines in bronchoalveolar lavage fluid (BALF) for differential diagnosis of lung cancer has been described in several studies6789101112. In our previous reports, we also observed that the levels of vascular endothelial growth factor (VEGF) and neuron-specific enolase (NSE) were significantly higher in BALF of lung cancer patients than in that of patients with benign diseases1314. Recently, transforming growth factor (TGF)-β1, interleukin (IL)-6, and tumor nectosis factor (TNF)-α were suggested in published studies as possible diagnostic biomarkers of lung cancer due to their higher concentrations in serum of lung cancer patients151617.…”
mentioning
confidence: 92%
“…circulating DNA in peripheral blood, circulating tumor-derived exosome, micro-RNAs, comparative protein profiling) in lung cancer diagnosis has been discussed and reviewed14. Recently, evaluation of VEGF-C and other tumor markers in bronchoalveolar lavage fluid showed ability of neuron-specific enolase for lung cancer diagnosis15. However, serum cytokine based markers to differentially diagnose lung cancer, its metastasis and COPD patients is not known to the best of our knowledge.…”
mentioning
confidence: 99%
“…In the views of some scholars , to obtain specimens for detection of tumor markers from the location of the tumor could be better than the blood specimens. If we detected the substance which were secreted into the pulmonary alveoli by cancer cell, some diagnostic value of peripheral lung cancer could be found.…”
Section: Introductionmentioning
confidence: 99%